Clinical characteristics of fibroblast growth factor receptor 3 antibody‐related polyneuropathy: a retrospective study. (20th March 2020) - Kovvuru, S.; Cardenas, Y. C.; Huttner, A.; Nowak, R. J.; Roy, B.
Abstract : Background and purpose: Autoantibodies are increasingly being used as a diagnostic biomarker of chronic inflammatory neuropathies. However, their role and associated clinical syndrome are not well defined. Methods: This retrospective chart review evaluated the clinical presentation, diagnostic workup and therapeutic responses in fibroblast growth factor receptor 3 (FGFR3) antibody‐associated neuropathy. Results: A total of 27 patients [14 men, aged 29–87 (65 ± 14) years] with positive FGFR3 antibody were included. Distal lower‐extremity paresthesia (66%), unsteady gait (26%) and foot drop (11%) were common presenting symptoms. Symptom onset was acute in four (15%) cases. Distal lower‐extremity weakness (mild in eight and severe in three patients) was the most frequent motor finding. Decreased distal sensation to pinprick (59%) and loss of vibration sensation (37%) were observed. Titer of FGFR3 ranged between 3100 and 30 000 (normal < 3000) with a mean of 10 688 ± 7284. Apart from the occasional association of other neuropathy‐related autoantibodies, comprehensive neuropathy workup was otherwise unrevealing. Six patients had other autoimmune disease and seven patients had a history of cancer. Electromyography reflected sensorimotor neuropathy with mixed axonal and demyelinating features in 11 cases. Pure sensory neuropathy was noted in three patients. Demyelination was found in five of six nerve biopsies. Intravenous immunoglobulin response was observed in 8/10 treated patients. Conclusions: The FGFR3 antibody appears not to be restricted to sensory neuropathy only. Its role in the pathogenicity of chronic inflammatory neuropathies is not yet well established and, although there may be a role for immunotherapy, larger studies are warranted.